A method for volumetric retinal tissue oxygen tension imaging - Felder, Anthony E. (Curr Eye Res, 2017)
PURPOSE: Inadequate retinal oxygenation occurs in many vision-threatening retinal diseases, including diabetic retinopathy, retinal vascular occlusions, and age-related macular degeneration. Therefore, techniques that assess retinal oxygenation are necessary to understand retinal physiology in health and disease. The purpose of the current study is to report a method for the three-dimensional (3D) imaging of retinal tissue oxygen tension (tPO(2)) in rats. METHODS: Imaging was performed in Long Evans pigmented rats under systemic normoxia (N = 6) or hypoxia (N = 3). A vertical laser line was horizontally scanned on the retina and a series of optical section phase-delayed phosphorescence images were acquired. From these images, phosphorescence volumes at each phase delay were constructed and a 3D retinal tPO(2) volume was generated. Retinal tPO(2) volumes were quantitatively analyzed by generating retinal depth profiles of mean tPO(2) (M(tPO2)) and the spatial variation of tPO(2) (SV(tPO2)). The effects of systemic condition (normoxia/hypoxia) and retinal depth on M(tPO2) and SV(tPO2) were determined by mixed linear model. RESULTS: Each 3D retinal tPO(2) volume was approximately 500 × 750 × 200 μm (horizontal × vertical × depth) and consisted of 45 en face tPO(2) images through the retinal depth. M(tPO2) at the chorioretinal interface was significantly correlated with systemic arterial oxygen tension (P = 0.007; N = 9). There were significant effects of both systemic condition and retinal depth on M(tPO2) and SV(tPO2), such that both were lower under hypoxia than normoxia and higher in the outer retina than inner retina (P < 0.001). CONCLUSION: For the first time, 3D imaging of retinal tPO(2) was demonstrated, with potential future application for assessment of physiological alterations in animal models of retinal diseases.